Bedside ultrasonography by emergency physicians for anterior talofibular ligament injury - Cem Gün (Journal of Emergencies, Trauma and Shock, 2013)
Objective: Our objective was to study the accuracy of emergency physician (EP) performed bedside ultrasonography (BUS) in patients with suspected anterior talofibular ligament (ATFL) injury. Materials and Methods: After a 6-h training program, from January to December 2011, an EP used BUS to prospectively evaluate patients presenting to the emergency department (ED) with suspected ATFL injury. Then, patients underwent ankle X-ray and Magnetic Resonance (MR) imaging. Outcome was determined by official radiology reports of the MR imaging. BUS and MR imaging results were compared using Chi-square testing. Results: Of the 65 enrolled patients, 30 patients were BUS positive. Of these, MR imaging results agreed with the BUS findings in 30 patients. In 35 cases, BUS was negative, and 33 of these were corroborated by MR imaging. The sensitivity, specificity, positive predictive value, negative predictive value, and negative likelihood ratio for BUS were 93.8%, 100%, 100%, 94.3%, and 0.06%, respectively. The diagnostic accuracy of BUS was not statistically different from MR imaging (K = 0.938, P = 0.001). Conclusion: BUS for the diagnosis of ATFL injury is another application of BUS in the ED. EPs can diagnose ATFL injury using BUS with a high degree of accuracy.